Cardiac‐specific down‐regulation of carnitine palmitoyltransferase‐1b (CPT‐1b) prevents cardiac remodeling in obese mice. Issue 12 (2nd November 2016) - Zhang, Yijie; Fang, Xianlong; Dai, Mingyan; Cao, Quan; Tan, Tuantuan; He, Wenbo; Huang, Yan; Chu, Liang; Bao, Mingwei
Abstract : Objective: To determine whether inhibiting cardiac carnitine palmitoyltransferase‐1b (CPT‐1b) improves obesity‐related cardiomyopathy. Methods: Four‐week‐old male C57BL/6J mice were fed with high‐fat diet (HFD) for 12 weeks to induce obesity. At 6 weeks of age, mice were subjected to intramyocardial injection with lentivirus to down‐regulate the expression of either cardiac CPT‐1b or green fluorescent protein. Morphological, biochemical, functional, histological, and ultrastructural profiles were assessed at 16 weeks of age. Results: HFD administration elicited obesity, cardiac hypertrophy, and systolic dysfunction accompanied with altered biochemical parameters. In addition, HFD consumption promoted lipid accumulation and reactive oxygen species generation in cardiomyocytes and damaged myocardial ultrastructure. Cardiac CPT‐1b silencing protected against HFD‐induced cardiac remodeling by decreasing heart weight/tibial length ratio and increasing left ventricular ejection fraction and fractional shortening, as well as normalizing left ventricular diameter. Meanwhile, CPT‐1b inhibition mitigated the changes in biochemical parameters, aggravated myocardial lipid accumulation, reduced intramyocardial reactive oxygen species production, and partly amended myocardial ultrastructural alterations in obese mice. Conclusions: Cardiac CPT‐1b suppression protects against the aggravation of cardiac morphology and function associated with HFD feeding. CPT‐1b represents a potential therapeutic target for the treatment of cardiac dysfunction related to metabolic diseases such as obesity and diabetes.